1995
DOI: 10.1002/jcp.1041640305
|View full text |Cite
|
Sign up to set email alerts
|

Control of matrix synthesis in isolated bovine chondrocytes by extracellular and intracellular pH

Abstract: The effects of extracellular and intracellular pH on matrix synthesis by isolated bovine chondrocytes were studied using radioisotope incorporation (35SO4 and 3H proline) and fluorescence techniques. Matrix synthesis exhibited a bimodal relation with decreased extracellular pH; with slight reductions (7.4 > pH > 7.1), synthesis increased (by up to 50%), whereas in more acidic media (pH < 7.1), synthesis was inhibited by up to 75% of control levels. The pHi was largely unchanged with extracellular acidity over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 27 publications
5
87
0
Order By: Relevance
“…For both disc and cartilage cells cultured for 48 h in alginate beads, the production of matrix components showed a biphasic response to pH (Fig. 1), as seen previously after short exposures of disc explants and cartilage cells in suspension culture to changes in extracellular pH [39,54]. Rates were highest at around pH 7.0-7.2 (the estimated pH in normal discs [19]), where they were 10-20% greater than at pH 7.4 (the extracellular pH of most body fluids).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…For both disc and cartilage cells cultured for 48 h in alginate beads, the production of matrix components showed a biphasic response to pH (Fig. 1), as seen previously after short exposures of disc explants and cartilage cells in suspension culture to changes in extracellular pH [39,54]. Rates were highest at around pH 7.0-7.2 (the estimated pH in normal discs [19]), where they were 10-20% greater than at pH 7.4 (the extracellular pH of most body fluids).…”
Section: Discussionsupporting
confidence: 75%
“…1a). Protein synthesis appeared less sensitive to pH, as observed in similar systems [39,54], but was still strongly inhibited under acid conditions (Fig. 1b).…”
Section: Discussionsupporting
confidence: 72%
“…Flow diagram representing the key stages of live cell volume buffered Dulbecco's modified Eagle's medium (DMEM), and imaging (square boxes). Each phase required optimization steps this initially provided a solution of 280 mosM (140 mM NaCl) (rounded boxes) that were necessary to both extract and view at pH 7.4; hence it was not necessary to supply C02 during the course of the experiment (11,34). Explants were posi tively labeled with 4.5 p.M 5-chloromethylfluorescein diacIn this paper we demonstrate a series of protocols for etate Molecular Probes, Eugene, OR) at 37 C for 15…”
Section: Methodsmentioning
confidence: 99%
“…Each of these physical phenomena may potentially act as a "mechano-ligand" activating or inhibiting one or more signaling pathways. Prior studies have often focused on the effects of one or a few of these components of compressive loading such as negative fixed charge density (26) or interstitial pH (22,29,30). Recent studies have also demonstrated that mechanical stretching of chondrocytes can increase nitric oxide production (31) and alter membrane transport phenomena, resulting in proliferative changes (32).…”
mentioning
confidence: 99%